2018
DOI: 10.1111/jocd.12712
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkles, brown spots, and cancer: Relationship between appearance‐ and health‐based knowledge and sunscreen use

Abstract: Despite most respondents reporting knowledge of health and appearance risks of sun exposure and a motivation to prevent them with sunscreen, most do not use sunscreen adequately. This discrepancy could be due to people perceiving risks of sun exposure based on duration of continuous exposure. There may be misconceptions that short-interval sun exposure that does not result in sunburn is less harmful than extended exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Among 400 participants, (89.0 %) were Saudi nationals, with (40.0 %) residing in the Abha city. The study results showed that women exhibited higher sunscreen usage than men ( Tilwani et al, 2018 ), which aligns with previous research highlighting women’s greater awareness of the health risks associated with UV radiation exposure ( Alsudairy et al, 2019 , Cao et al, 2019 ). Furthermore, the results revealed that (59.8 %) of the participants were female, while (40.3 %) were male.…”
Section: Discussionsupporting
confidence: 89%
“…Among 400 participants, (89.0 %) were Saudi nationals, with (40.0 %) residing in the Abha city. The study results showed that women exhibited higher sunscreen usage than men ( Tilwani et al, 2018 ), which aligns with previous research highlighting women’s greater awareness of the health risks associated with UV radiation exposure ( Alsudairy et al, 2019 , Cao et al, 2019 ). Furthermore, the results revealed that (59.8 %) of the participants were female, while (40.3 %) were male.…”
Section: Discussionsupporting
confidence: 89%
“…The increased rate of facial care product use in the patients diagnosed with hair disorders might rather be explained by coincidence. Previous studies reported several factors that influence sunscreen use, including female sex, higher education, higher income, and higher skin cancer risk, 14,15 larger perceived skin cancer risk reduction, 16 greater photoaging knowledge, 17 frequent exercise, and also recent doctor visits. 14 Taken together, the aforementioned findings and evidence seem to suggest that that people who are concerned about their appearance and who frequently follow-up with a dermatologist may be more motivated to regularly apply facial care products, particularly sunscreen.…”
Section: Ta B L Ementioning
confidence: 99%
“…2 Some counseling strategies are more effective than others to promote sunscreen use: patients are more likely to use sunscreen when counseled using a gain-framed approach, emphasizing the benefits of using sunscreen to prevent skin cancer and photoaging. 3,4 Based on the results of our study, a variety of approaches may be helpful for increasing sun protective behavior. Using descriptive language and photographs of skin cancer and the implications of its treatment, including surgical defects created to remove these cancers, may be a promising approach, though one limitation our study is that reported likeliness to use sunscreen may not be reflective of real-world sunprotective behavior.…”
Section: Dear Editormentioning
confidence: 88%
“…1 Patient motivation for sunscreen use is impacted by both health and appearance, as patients use sunscreen to avoid skin cancer, wrinkles, and age spots. 3 Patient education increases the likeliness of sunscreen use. 2 Some counseling strategies are more effective than others to promote sunscreen use: patients are more likely to use sunscreen when counseled using a gain-framed approach, emphasizing the benefits of using sunscreen to prevent skin cancer and photoaging.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation